Eastern Samar Development Foundation Inc. (ESADEF INC.) Focus on its democratization and development. - Igdalino, Lourdes R. (Lourdes R. Igdalino, 2009)
NGOs in the country continue to proliferate and captured the attention of different researchers. These Non-Governmental Organizations are widely dispersed in different places in the country. They have different focus and objectives, from protecting the rights of women to helping the environment and helping the farmers and fishermen.